Hysterectomy for benign disease: clinical practice guidelines from the French College of Obstetrics and Gynecology. (July 2016) - Deffieux, Xavier; Rochambeau, Bertrand de; Chene, Gautier; Gauthier, Tristan; Huet, Samantha; Lamblin, Géry; Agostini, Aubert; Marcelli, Maxime; Golfier, François
Abstract: Objective: The objective of the study was to draw up French College of Obstetrics and Gynecology (CNGOF) clinical practice guidelines based on the best available evidence concerning hysterectomy for benign disease. Methods: Each recommendation for practice was allocated a grade, which depends on the level of evidence (clinical practice guidelines). Results: Hysterectomy should be performed by a high-volume surgeon (>10 hysterectomy procedures per year) (grade C). Stimulant laxatives taken as a rectal enema are not recommended prior to hysterectomy (grade C). It is recommended to carry out vaginal disinfection using povidone-iodine solution prior to hysterectomy (grade B). Antibiotic prophylaxis is recommended during hysterectomy, regardless of the surgical approach (grade B). The vaginal or laparoscopic approach is recommended for hysterectomy for benign disease (grade B), even if the uterus is large and/or the patient is obese (grade C). The choice between these two surgical approaches depends on other parameters, such as the surgeon's experience, the mode of anesthesia, and organizational constraints (duration of surgery and medical economic factors). Vaginal hysterectomy is not contraindicated in nulliparous women (grade C) or in women with previous cesarean section (grade C). No specific hemostatic technique is recommended with a view to avoiding urinary tract injury (grade C). In the absence of ovarian disease and a personal or family history of breast/ovarian carcinoma, the ovaries should be preserved in pre-menopausal women (grade B). Subtotal hysterectomy is not recommended with a view to reducing the risk of peri- or postoperative complications (grade B). Conclusion: The application of these recommendations should minimize risks associated with hysterectomy.